REKONSTRUKSI HAK ANAK PASCAKELAHIRAN DALAM PERSPEKTIF ISLAM: ANALISIS NILAI SPIRITUAL, PENDIDIKAN, DAN KEMANUSIAAN BERBASIS TARBIYATUL ATHFĀL - Mu'adz Haidar Zulkarnain; Faqihuddin Akbar Mu’allim; Idham Kholid; Erlina; Fachrul Ghazi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study reconstructs the concept of children’s post-birth rights from an Islamic perspective by positioning spiritual, educational, and humanitarian values as the foundational principles of early child upbringing. Departing from contemporary approaches that tend to emphasize legal and physical aspects while marginalizing spiritual dimensions, this research re-examines Islamic teachings through the classical text Tarbiyatul Athfāl. A qualitative library-based approach is employed, using thematic analysis within the framework of maqāṣid al-sharī‘ah. The findings demonstrate that children’s rights in Islam extend beyond physical care and legal recognition to encompass the cultivation of spiritual consciousness, moral character, and human dignity from birth. Spiritual values are embedded in practices such as the recitation of the adhan, tahnik, giving meaningful names, and performing aqiqah, which function as early internalization of monotheism and Islamic identity. Educational values are reflected in parenting based on role modeling, affection, and continuous moral habituation. Meanwhile, humanitarian values emphasize protection, welfare, and respect for children as dignified human beings. This reconstruction affirms that Islamic teachings provide a holistic and integrative framework for safeguarding children’s post-birth rights and remain highly relevant in addressing contemporary challenges in child education and upbringing.